1975
DOI: 10.1149/1.2134316
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Permeability of Stabilized Zirconia Solid Electrolytes

Abstract: The oxygen permeability of solid electrolytes 85.0 mole per cent (m/o) ZrO~ -]-15.0 m/o CaO (I), 90.0 m/o ZrO2 -p 10.0 m/o Y208 (II), 89.0 m/o ZrO2 -t-8.0 m/o Y203 -}-3.0 m/o A120,~ (II1), 90.0 m/o ZrO2 + 10.0 m/o Sc203 (IV) is investigated at temperature range 900~176and partial pressures of oxygen 0.01-1.0 arm. The oxygen permeability in this range of oxygen pressures is proportional to Po21/4. It is shown that the diffusion coefficient of oxygen does not depend on its pressure in a gas atmosphere. Transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

1975
1975
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 2 publications
2
23
0
Order By: Relevance
“…Indeed for the thick oxide films the experimental results are consistent with the theoretical prediction (Alcock and Chan, 1972;Palguev et al, 1972;Fouletier et al, 1976;Dou et al, 1985;Park and Blumenthal, 1989;Bouwmeester et al, 1992). It is obvious, however, that the surface charge transfer reactions can be very important when the oxygen transport resistance in the bulk oxide becomes very small as a result of the increase in ionic and electronic conductivities or the decrease in film thickness.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Indeed for the thick oxide films the experimental results are consistent with the theoretical prediction (Alcock and Chan, 1972;Palguev et al, 1972;Fouletier et al, 1976;Dou et al, 1985;Park and Blumenthal, 1989;Bouwmeester et al, 1992). It is obvious, however, that the surface charge transfer reactions can be very important when the oxygen transport resistance in the bulk oxide becomes very small as a result of the increase in ionic and electronic conductivities or the decrease in film thickness.…”
Section: Introductionsupporting
confidence: 83%
“…In Figure 1 an oxide membrane is schematically divided into the bulk oxide and the adjacent interfaces, emphasizing both solid state diffusion and surface electrochemical reactions in the mass transport of the oxygen species. Among the limited experimental studies on oxygen permeation through fast ionic conductors, almost all studies focused on the oxygen permeation through relatively thick (> 500 pm) stabilized zirconia films which are essentially ionic conductors (Alcock and Chan, 1972;Palguev et al, 1972;Fouletier et al, 1976;Dou et al, 1985;Park and Blumenthal, 1989;Bouwmeester et al, 1992). In these studies, most researchers considered only the oxygen transport through the bulk oxide.…”
Section: Introductionmentioning
confidence: 99%
“…[2], [4], [8], and [9]), it is found that the film growth rate is determined by the substrate pore structure (r, L), the diffusivity of oxygen source reactant in the substrate pore (Dw or Do), electrochemical transport properties (%o and a,~ charge-transfer reaction rate constants (a2 and ~4), and experimental conditions (controllable parameters Pw, Pc(w), and T). In principle, all these parameters except Pc(m) are known or available from experiments [e.g., oxygen permeation through YSZ pellets (14)(15)(16)(17)]. The oxygen partial pressure in the metal chloride vapor, Pc(m), is the value equilibrated with the metal oxides and chlorides in the chloride chamber.…”
Section: Theoreticalmentioning
confidence: 99%
“…[14] gives the following H(t) relation, for the case when P~w) and Po(~ are very low so that the first term in Eq. [14b] is neglected [16] which is the same as the model equation developed by Carolan and Michaels [6]. In this situation, H(t) is parabolic.…”
Section: Kinetics Evd Processmentioning
confidence: 99%
“…Region of usual diffusion coefficient in oxides Ag(Agl) [3] Li ll [2] 0.5 Figure 1 O(CSZ) [7] ""~ ______ Na(~-AI203) […”
mentioning
confidence: 99%